An Analysis of Prospective Mathematics Teachers' Knowledge about Zeno's Paradox of Motion - Fitri Fauziyyah; Yulyanti Harisman (Jurnal Pendidikan Matematika (JPM), 2025)
Paradoxes are catalysts for innovation or new findings in mathematics. One of them comes from Zeno's thoughts, namely Zeno's paradox. Zeno's paradox of motion remains relatively unknown among students. This study aims to describe Zeno's paradox of motion to readers and explore the extent of knowledge of prospective mathematics teacher students about Zeno's paradox of motion. This qualitative study employs a literature review and case study approach, while the instrument used is an open-ended interview. The literature review was conducted by reviewing articles to find out the paradox of Zeno's motion. Case studies were conducted by interviewing ten 2023 students as research subjects, taken randomly from five available classes in the mathematics education study program. The literature review provided a foundational understanding of the paradox, and the case studies offered empirical insights into its cognitive implications within a specific educational context. The data analysis used was thematic. This study reveals that there are 2 categories of student knowledge about Zeno's paradox of motion, including 1) Unknown of Zeno Motion Paradoxes, and 2) Known of Zeno Motion Paradoxes. This underscores the importance of incorporating historical mathematical paradoxes into teacher training to enrich students' understanding of mathematical evolution and critical thinking.